Perovskitas La1-xSrxMnO3, suportadas em alumina e zircônia, aplicadas à combustão do metano - Santos, Lidiane Faria (Universidade Federal de São Carlos, 2007)
The total oxidation of the methane is an important environmental and industrial reaction, mainly because it is extensively used in energy production and in the control of gases emission to the atmosphere. With catalysts, the methane combustion is available at lower temperatures, thus decreasing the emission of NOx, a gas of green house harmful to human health. Perovskite-type oxides of the series La1-xSrxMnO3 (x = 0, 0,3 e 0,5) supported on γ-Al2O3 and ZrO2 were prepared and characterized for application in methane oxidation. The samples were prepared by co-precipitation and depositionprecipitation methods, using aqueous solutions of metals nitrates and urea as precipitant agent. Each catalysts were calcined in two steps: first at 600 ºC for 5 hours and later in one of these conditions: 700 ºC/10 h, 800 ºC/10 h or 900 ºC/10 h. Chemical analysis, X-Ray Diffraction (XRD), Specific Surface Area (BET), Temperature Programmed Reduction (TPR) and Scanning Electron Microscopy (SEM) were applied to characterize the samples. The XRD spectra showed that the crystalline structures of the unsupported La1-xSrxMnO3 perovskite were best defined with the increase of the calcination temperature. On the other hand, in the supported samples the complete visualization of the XRD spectra was difficult, being the perovskite structure just confirmed by the presence of its more intense peak. As La3+ and Sr2+ do not reduce at the experimental conditions applied in this work, all the peaks showed in TPR analysis corresponding to reduction of the species Mnn+. The influence of the calcination temperature can also be observed in the variation of the specific surface area of the catalysts. The catalytic essays showed that the compounds are actives at relatively low temperature. The supported catalysts presented higher activity than the unsupported ones and the calcined at lower temperature showed more satisfactory catalytic activities. The substitution of La by Sr increased significantly the catalytic activity of the studied systems
Keywords: Catálise heterogênea; Reforma - metano; ENGENHARIAS::ENGENHARIA QUIMICA